Decomposition and/or hydrogenation of hydrogen peroxide over Pd/Al2O3 catalyst in aqueous medium: factors affecting the rate of H2O2 destruction in presence of hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Hydrogen peroxide destruction by its decomposition and/or hydrogenation to water in the presence of H-2 over Pd(5 wt.%)/Al2O3 catalyst in an aqueous reaction medium, similar to that used in the H-2-to-H2O2 oxidation, has been thoroughly investigated at different reaction conditions. The H2O2 destruction is strongly influenced by the oxidation state of Pd in the catalyst and also by the presence of different halide anions (viz. F-, Cl-, Br- and I-) in the acidic aqueous medium or in the catalyst, depending upon the concentration of halide anions. The cations associated with halide anions have, however, a little or no influence on the H2O2 destruction. The iodide anions strongly poisoned the catalyst, even at their very low concentration. The fluoride anions have only a small effect on the H2O2 destruction. The chloride or bromide anions drastically inhibit the rapid H2O2 decomposition, but promote the slower H2O2 hydrogenation. The H2O2 destruction reactions are strongly influenced by the halide anion and acid concentrations. The presence of acid (protons) plays a very important role in drastically reducing the H2O2 destruction, particularly in the presence of chloride anions. Both in the presence and absence of Cl- or Br- anions, the H2O2 destruction activity of the catalyst is markedly reduced because of the oxidation of Pd but it is drastically increased due to the presence of H-2. A plausible reaction mechanism for the rapid H2O2 decomposition and slower H2O2 hydrogenation reactions, prevailing under the different reaction conditions, has also been discussed. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: decomposition of H2O2; halide anions as catalyst promoter or indicator; Hydrogen peroxide; hydrogenation of H2O2; Pd/Al2O3